Microaggressions and racial privilege within the social work profession: The social work licensing examinations. Issue 2 (3rd April 2019) - Castex, Graciela; Senreich, Evan; Phillips, Norma Kolko; Miller, Conard Mark; Mazza, Carl
ABSTRACT: Passing standardized examinations is a requirement for different levels of social work licensure throughout the United States. In all 50 states, exams produced by the Association of Social Work Boards (ASWB) are utilized for this purpose. Using critical race theory as a framework, this article discusses how these licensing tests may create a barrier to professional advancement for social workers who have not had educational advantages, resulting in marginalization of many talented non-white and immigrant social workers needed in the field. In addition, this article identifies specific racial microaggressions present in a 48-item practice licensing exam published by ASWB.